IDENTIFICATION OF STUDENTS' MISCONCEPTIONS IN STATISTICS USING A THREE-TIER DIAGNOSTIC TEST BASED ON ASPECTS AND LEVELS OF UNDERSTANDING - Maghfiroh, Wasiattul; Supriyo, Supriyo; Nurmalitasari, Dewi (Cahaya Ilmu Bangsa Institute, 2024)
This study aims to determine the location of false beliefs that most often occur in students in statistics material and to determine the percentage of students' misconception level in statistics material based on its aspects. This research uses descriptive qualitative method with sampling using purposive sampling technique. The subjects of this study were students of class X-2 SMA Negeri 1 Grati, Pasuruan Regency. The instrument used is a three-tier diagnostic test question consisting of 5 items that have been validated by experts. The results of this study indicate that students' misconceptions about statistics material are generally experiencing moderate misconceptions. In the data obtained, as many as 15% show student misconceptions that fall into the category of understanding the concept, 54% show student misconceptions that fall into the category of not understanding the concept, and 31% show student misconceptions. The most common misconception in statistics material is in the misconception aspect of arithmetic at 75%. Meanwhile, the results of other misconceptions show that 8% of students have translation misconceptions, 44% have sign misconceptions, 75% have calculation misconceptions, 69% have strategy misconceptions, and 69% have systematic misconceptions.